Methods and Analysis of Assessment of The Level of Economic Efficiency - Umirova Gulmira Shodiboy kizi (Academia Open, 2025)
General Background: Economic efficiency assessment plays a crucial role in guiding strategic and financial decision-making across industries. Specific Background: In the construction sector, evaluating enterprise-level efficiency remains a complex task due to diverse operational factors and inconsistent application of assessment tools.Knowledge Gap: Existing literature offers various models such as cost-benefit analysis, efficiency ratios, DEA, and stochastic frontier analysis; however, limited studies critically compare these methods or explore their integrated applicability to real-world construction industry data. Aims: This study aims to analyze and compare methods for assessing economic efficiency, with a focus on construction enterprises, and to propose a robust evaluation framework. Results: The analysis demonstrates that different tools capture varying dimensions of efficiency, with DEA and the DuPont model offering complementary insights when applied to enterprise data. Novelty: The article introduces a comprehensive evaluation model that integrates quantitative and qualitative indicators, addressing methodological limitations and enhancing contextual relevance. Implications: Findings underscore the need for tailored assessment strategies that align with organizational objectives, and suggest future directions for refining hybrid models to support sustainable economic planning and resource optimization in industrial enterprises. Highlights: Highlights comparative analysis of efficiency assessment methods. Emphasizes integrated use of quantitative and qualitative tools. Offers practical implications for strategic economic planning. Keywords: Economic Efficiency, Construction Industry, DuPont Model, Data Envelopment Analysis, Performance Evaluation